Graduate studies on optoelectronics in Argentina: an experience - Fernández, Juan Carlos (2014)
The number of graduate programs in Optoelectronics in Argentina is scarce. The current Optics and Photonics Education Directory lists only three programs. One of them was launched in 2001 in the Facultad de Ingeniería (College of Engineering), Universidad de Buenos Aires (UBA). This was the first graduate program in the field, leading to a Master Degree in Optoelectronics. This decision arose from the demand of telecommunications industries and several estate- or private-funded research institutions working with us in the fields of lasers, optics, remote sensing, etc. A great bonus was the steady work, during several decades, of research groups in the College on the development of different type of lasers and optical non destructive tests and their engineering applications. As happened in many engineering graduate programs in Argentina at that time, few non full-time students could finish their studies, which called for 800 hours of traditional lecture-recitation classes, and the Master Thesis. In recent years Argentine Education authorities downsized the Master programs to 700 hours of blended learning and we redesigned the Graduate Optoelectronic Engineering Program to meet the challenge, dividing it in two successive one year programs, the first aimed at a professional training for almost immediate insertion in the labor market (called Especialización en Ingeniería Optoelectrónica), and the second (called Maestría en Ingeniería Optoelectrónica y Fotónica) aimed at a more academic and research target to comply with the UBA standards for Master degrees. The present work is a presentation of the new program design, which has begun in the current year. © (2014) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.